The effect of piezoelectric surgery implant osteotomy on radiological and molecular parameters of peri‐implant crestal bone loss: a randomized, controlled, split‐mouth trial. Issue 5 (16th June 2015) - Peker Tekdal, Gözde; Bostanci, Nagihan; Belibasakis, Georgios N.; Gürkan, Ali
Abstract: Aim: To evaluate the effect of piezoelectric surgery (PS) implant osteotomy on biochemical and radiological parameters of crestal bone (CB) loss. Material and methods: In this randomized, controlled, clinical study, 38 osteotomies were prepared with PS and drilling in the posterior maxilla in a split‐mouth design. Implants were placed and left for non‐submerged healing. Osteotomy time, insertion torque, pain perception, probing depth, and modified gingival and plaque indices were recorded. Peri‐implant sulcular fluid (PISF) was collected from four sites of each implant at 2, 4, 8, 12, and 24 weeks. PISF samples were analyzed by ELISA for receptor activator of nuclear factor kappa‐B‐ligand (RANKL) and osteoprotegerin. CB loss was assessed on periapical radiographs at the 12th and on cone beam computed tomography (CBCT) at the 24th weeks. The influence of time and osteotomy method on biochemical and radiological parameters of CB loss employed statistical method of Brunner–Langer. Results: Osteotomy time for PS group was significantly longer than the drill group ( P < 0.05). Pain perception that was lower in the PS than in the drill group depended on osteotomy method ( P < 0.05). PS group had lower RANKL total amount than the drill group ( P < 0.05). Mean CB loss on periapical radiographs at the 12th week for PS and drill groups were 0.11 and 0.18 mm, respectively ( P > 0.05). At the 24th week, PS and drill groups showed 0.11 and 0.12 mm CB losses on CBCT, respectively ( P > 0.05). However, CB loss values did not depend on osteotomy modality ( P > 0.05). Conclusion: PS may modify and reduce bone‐destructive inflammatory response during implant osseointegration. Therefore, on the molecular level, it might be a less traumatic osteotomy modality than drilling although this was not reflected by CB loss values in the present study.